OPTIMALISASI POTENSI LOKAL MELALUI PEMANFAATAN KOTORAN SAPI MENJADI PUPUK ORGANIK DI DESA PRINGGASELA TIMUR - Husaidi, M. Malki; Jurnal Wicara; Maharani, Shella; Widhiyantara, I Nyoman; Dewi, Ni Nengah Sunia Ardita; Rahayu, Melitha Shawwira; Arung, Elsa Batari Teja; Sawitri, I Gusti Ayu Vega; Alvina, Reva Mei; Yusmita, Eliza; Haris, Khaekal Danial (Jurnal Wicara, 2025)
The Community Empowerment Village Service Learning Program (KKN-PMD) of Mataram University in Pringgasela Timur Village, Pringgasela Subdistrict, East Lombok Regency, was conducted to optimize the potential use of natural waste derived from livestock waste, plant residues, and other organic materials as a source of organic fertilizer through innovative compost processing. This activity aims to enhance the technical skills of the community in organic fertilizer production and its application. The method used is Participatory Action Research (PAR) involving the residents of Pringgasela Timur Village. The activity was carried out in several stages, starting with awareness-raising sessions on organic fertilizer and training in organic fertilizer production. From this community service activity, it can be concluded that there has been an increase in the skills and knowledge of the community in Pringgasela Timur Village, particularly the residents, in processing livestock waste into organic fertilizer up to its application. The attendance rate was 97.25% of the target.